IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF DALAM MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA 4-5 TAHUN DI TK MUSLIMAT NU II PANGORAYAN - Lailatul Qomariyah; Mohammad Subhan (Journal of Education Partner, 2023)
PAUD is an effort to foster children aged 0-6 years through the provision of stimulation as an effort to help their growth and development. Early childhood is often known as the golden age, which at this time is the most appropriate period to provide the main basis for developing the various potentials possessed by children. Aspects of social emotional development is one aspect of development that must be optimized in children, which will determine the attitudes and behavior of children as adults. One of the efforts to be able to help children's social emotional development, suitable learning methods are needed to be applied to the learning process. One of them is the application of cooperative learning methods. In this study, using descriptive qualitative research methods, with research subjects aged 4-5 years at TK Muslimat NU II Pangorayan as many as 20 students. The purpose of this study was to describe in depth the implementation and impact of cooperative learning in developing social-emotional children 4-5 years in TK Muslimat NU II Pangorayan. Based on the research that has been done, the application of cooperative learning methods in an effort to help the socio-emotional development of children in TK Muslimat NU II Pangorayan is considered successful. This can be seen from changes in children's attitudes which are characteristics and indicators of children's social emotional development, including self-awareness, sense of responsibility and social behavior